Pengembangan Modul IPA Berbasis Metode Studi Kasus untuk Siswa Sekolah Menengah Pertama: Development of Method Based Science Module Case Study for Junior High School Students - Raifa Novriani; Asni Johari; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2017)
Active learning requires the existence of teaching materials that are appropriate to students conditions and meet students’ needs. This study aims to (i) produce a science learning module based on the case study method used as teaching material, (ii) reveal the quality of media developed in terms of content, appearance, and attractiveness, and (iii) study the process of developing a case study science learning module for middle school students. This research is a type of research and development. The product developed was validated by a media expert and learning material expert. The product trial was carried out in two steps, namely small group trials and large group trials. The subjects of the trial consisted of six students (small group trials) and 30 students (large group trials), all of whom were students of grade VII of SMPN 3 Tanjung Jabung Timur. The data collected from media experts and learning material experts as well as form science teacher and students. Data were analyzed using descriptive analysis. The results of this study can be concluded that the development of a science module based on case study methods was declared feasible to be used in learning activities based on the results of material and media expert validation. Based on the results of student and teacher responses, the science module based on a case study method is very good to be used as teaching material in schools.